Topology optimization design and numerical analysis on cold plates for lithium-ion battery thermal management. (February 2022) - Chen, Fan; Wang, Jiao; Yang, Xinglin
Highlights: The cold plates of battery liquid cooling system are designed by topology optimization. Consider the two cold plate models the inlet and outlet on the centerline or the diagonal. Compare the numerical results of design cold plates with rectangular-channel and serpentine-channel cold plates. Topology optimization cold plates have better cooling performance and lower flow resistance at the same inlet pressure. The change of inlet pressure has an impact on the cooling effect of the cold plates. Abstract: In this paper, the cold plates are designed to cool the rectangular lithium-ion battery packs by the topology optimization method. The topology optimization method obtains the channel structure in the two-dimensional model, and three-dimensional cold plate models are then established according to their two-dimensional structure. In a simple model for a battery pack, numerical analyses of topology optimization cold plate (TCP) are implemented using COMSOL software. Numerical results were compared with conventional rectangular-channel cold plate (RCP) and serpentine-channel cold plate (SCP) to investigate the cooling performance and flow characteristics of the cold plate. The results demonstrate that the flow channel structure of the cold plate has a significant influence on the temperature distribution of the battery. At 150 Pa inlet pressure, the maximum temperature of batteries with TCPs is reduced by 0.27% and 1.08% compared to that with RCP or SCP, and the temperature difference is lowered by 19.50% and 41.88%. Appropriately increasing the inlet pressure of the cold plate can also reduce the maximum temperature and temperature difference of batteries. Due to low flow resistance and high heat transfer coefficient, topology optimization will be widely used to design battery cold plates.